PELAYANAN PUBLIK DAN WELFARE STATE - Rofieq, Ainur (Magister Ilmu Pemerintahan, Program Pascasarjana Universitas Islam, 2011)
Political reforms that happened in Indonesia were not able to produce significant improvement, one in the public service sector. People do not receive the public services that are transparent, accountable, efficient and responsive. The result of the public services is not improved people?s welfare. This paper considers the characteristics of a form of public service that supports the establishment of the welfare state.